Enhancing the Patient Safety Program in Community Health Centers: The Role of Partnership as Middle Line in Optimizing Continuous Quality Improvement - Haunan, Muhammad Hafiz; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: The quality of health services at community health centers, as a first-level health care facility, must be continuously improved to ensure patient safety. However, there are still many challenges in implementing an optimal patient safety program, especially related to the role and function of the Patient Safety Team and Quality Assurance Officer. Method: This study analyzed the organizational structure and effectiveness of the patient safety program at community health centers, based on Mintzberg's organizational model. It evaluates the role of internal and external resources in improving patient safety and proposes structural changes through the concept of partnership to improve patient safety program implementation. Results: The results showed that the implementation of patient safety at the community health center was not optimal, where the many duties of the Quality Team as Middle Manager led to neglect of the main functions in the patient safety quality improvement program. This resulted in ineffective patient safety practices and a lack of safety culture among health workers. This study demonstrates the benefits of a partnership concept to replace the Quality Team. With the implementation of the partnership concept, PHCs can partner with external agencies such as university research centers or consulting agencies as the middle line, which helps in regular monitoring and evaluation, thereby improving the effectiveness and efficiency of the patient safety program at the PHC. External resources can assist in monitoring and evaluation, allowing the Quality Team to focus on other tasks while outsourcing external resources to the patient safety program. Conclusion: Adopting the partnership concept in the organizational structure of community health centers can improve the implementation of patient safety in a sustainable manner. This approach can increase operational efficiency, improve service quality, and build public trust in the health center.